Numerical simulation to determine the fracture aperture in a typical basin of China. (1st January 2021) - Liu, Jingshou; Yang, Haimeng; Bai, Jianping; Wu, Kongyou; Zhang, Guanjie; Liu, Yang; Xiao, Zikang
Highlights: A numerical simulation method based on the finite element method is presented for determining fracture aperture. The mathematical relationship between multiple factors and fracture aperture is determined. When the fracture spacing is less than 2 m, the fracture spacing is positively correlated with the fracture aperture. Abstract: Fracture aperture is the main source of uncertainty in reservoir fracture modeling; this uncertainty is due to the difficulty of accurately quantifying underground fracture aperture and the limited understanding of the main factors controlling fracture aperture and the mechanical deformation process. The theoretical evaluation model of underground fracture aperture is a key aspect of fracture characterization and modeling of tight sandstone reservoirs. Based on the self-similarity theory of rock fractures and considering the 3D morphology of a fracture surface, a finite element geomechanical model of a fracture surface is established. A combination of physical experiments and numerical simulations is used to determine the fracture apertures in underground reservoir conditions. Furthermore, a theoretical model of fracture aperture is proposed under the constraints of the in situ stress, rock mechanics parameters, fracture occurrence, fracture scale, fracture filling characteristics and fracture surface characteristics. According to the vertical distribution model of in situ stress, the theoretical average fracture aperture in rock at different depths is determined. With increasing burial depth, the fracture aperture decreases. When the horizontal stress difference is greater than 10 MPa, the effect of the in situ stress difference on the average fracture aperture decreases. Among the three fracture filling patterns considered, the average effective aperture of fractures with uniform filling is the largest. When the fracture spacing is less than 2 m, the fracture aperture increases with increasing fracture spacing; when the fracture spacing is greater than 2 m, the fracture aperture is basically unaffected by the fracture spacing.